Service time window selection for attended home deliveries: a case study for urban and rural areas - Melanie Burian; Charlotte Köhler; Ann Melissa Campbell; Jan Fabian Ehmke (Central European Journal of Operations Research, 2023)
Attended home deliveries are one of the most challenging logistics services with different customer expectations and challenges in urban and rural areas. For different demand densities, retailers must strike a balance between providing excellent customer service and optimizing routing efficiency. While customers often expect delivery promises with narrow time windows, research has demonstrated that longer time windows can increase the flexibility and the ability to accept more customers. However, it is not clear how different demand densities impact flexibility and customer acceptance. To serve as many customers as possible with excellent service quality, this paper reviews and expands on ideas for offering short and long time windows in a flexible manner in urban and rural areas. This study proposes different methods for providing customers with time windows of different lengths and investigates their performance based on a case study in Vienna and Upper Austria.
Keywords: 650; Delivery area; Routing flexibility; Service planning; Attended home delivery; Vehicle routing with time windows